A new species of Cirrhicera Thomson, 1857 from Mexico, and redescription of Anisopodus acutus Thomson, 1865 (Coleoptera, Cerambycidae, Lamiinae) - Santos-Silva, Antonio; Galileo, Maria Helena M.; Tirant, Stéphane Le (Zootaxa, 2017)
A new species of Cirrhicera Thomson, 1857 is described from Mexico and included in a previous key. Anisopodus acutus Thomson, 1865 is redescribed and recorded for the first time in Ecuador.